Memperpanjang Kesegaran Bunga Potong Krisan (Dendranthema grandiflora Tzvelev.) dengan Larutan Perendam Sukrosa dan Asam Sitrat - WIRAATMAJA, I WAYAN; GEDE ASTAWA, I NYOMAN; DEVIANITRI, NI NYOMAN (AGRITROP; Vol. 26, No. 3 September 2007, 2012)
Research on prolonging vase life of chrysanthemum aimed to recognize some concentration of sucrose and citric acid applied on solution to prolong vase life of chrysanthemum. Randomized Block Design was applied on this research with two factors. First factor was concentration of sucrose, consisted of four levels which were 0, 2, 4, and 6 percent of sucrose. Second factor was concentration of citric acid, consisted of four levels which were 0, 200, 400, and 600 ppm of citric acid. All combination treatments were replicate two times. Variables which were observed in this experiment i.e.: vaselife, percentage of full bloom, percentage of flower wilting, and total of absorbed solution. The results showed that the longest vase life of chrysanthemum cut flower was found on sample treated by 2.70% of sucrose combined with 400 ppm of citric acid. The longest vase life was 13.02 days or 6.02 days longer than control.
Keywords: chrysanthemum , sucrose, and citric acid